Management of Radioactive Spills in Nuclear Medicine; Teaching and Assessing with Objectively Structured Assessment of Technical Skills - Riffat Hussain (World Journal of Nuclear Medicine)
Routine work in nuclear medicine requires the careful elution of radioactivity and its subsequent, storage and handling. Though all effort is maintained to prevent any "spill" of this radioactivity, accidents are bound to happen. The response to this spill is a methodically worked out a plan that is written and adopted as a "standard operating procedure." This protocol is taught to all involved in the area of working as a mock drill/apprenticeship model. No formal evaluation of learning is in place except for the mock drills. The objectively structured assessment of technical skills (OSATS) is a variation on the Objective Structured Clinical Examination, which is a form of workplace based assessment. The OSATS is cited in the Accreditation Council of Graduate Medical Education evaluation toolbox on the website as the most desirable evaluation tool for the patient care topics. It is the objective of this paper is to introduce the "OSATS" for teaching, and assessment of the learning, of the protocol for the management of radioactive spill. As a review of the literature on the subject failed to reveal any such teaching protocol/material/document for this important technical skill, we hope that it may act as a landmark for the development of teaching and assessment of other technical skills also.